2017
DOI: 10.4172/2469-6676.100122
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Development within the Family: Attachment Dynamics and Parental Attitudes in Cross-Sectional and Longitudinal Studies

Abstract: Context: Body image is the subjective representation of one's own body and has different component. Body dissatisfaction is linked to low self-esteem and unhealthy behaviors and it is recognized to be at the core of eating disorders psychopathology, therefore many studies search for its determinants. Family is the critical environment where early development and psychological maturation occur and family dynamics seem to play a significant role in body image development. Objective and methods:The scope of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These beauty representations usually set extremely high practically unachievable standards. Literature reviews indicated that body appearance issues and eating disorders are more prevalent in women, especially adolescents and young adults [8,9]. Especially notable is the emphasis on thinness in women across all age groups, and the overall presentation of the female body as attractive rather than functional.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These beauty representations usually set extremely high practically unachievable standards. Literature reviews indicated that body appearance issues and eating disorders are more prevalent in women, especially adolescents and young adults [8,9]. Especially notable is the emphasis on thinness in women across all age groups, and the overall presentation of the female body as attractive rather than functional.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effects of family characteristics and body image are mostly concerned with eating disorders [8]. Parents’ actions and beliefs, their implicit and explicit communication with the child, have a significant effect on the child [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A statistically nonsignificant influence is found between the two variables of paternal relationship and body image. Many research have supported the impact of parental relationship on body image of a daughter (Amianto et al, 2017;Dohnt & Tiggemann, 2006;Michael et al, 2014;Phares et al, 2004) but there have been contradictions as other studies have tapped multiple external factors of influence on a woman's body image. Body image disturbances have found to be more common in girls than boys.…”
Section: Discussionmentioning
confidence: 99%